Challenging obesity, diabetes, and addiction: the potential of lorcaserin extended release - Hurt RT (Dove Medical Press, 2018)
Ryan T Hurt,1–4 Manpreet S Mundi,3 Jon O Ebbert5 1Division of General Internal Medicine, Mayo Clinic, Rochester, MN, USA; 2Division of Gastroenterology and Hepatology, Mayo Clinic, Rochester, MN, USA; 3Division of Endocrinology, Diabetes, Metabolism and Nutrition, Mayo Clinic, Rochester, MN, USA; 4Division of Gastroenterology, Hepatology and Nutrition, University of Louisville, Louisville, KY, USA; 5Division of Primary Care Internal Medicine, Mayo Clinic, Rochester, MN, USA Abstract: Obesity is a global epidemic that is a leading cause of preventable death. In addition to lifestyle modification, there are numerous obesity treatments for clinicians to consider, including medications. Lorcaserin immediate release/extended release (IR/XR) is a US Food and Drug Administration approved medication for overweight and obese patients to be used with lifestyle modifications. Lorcaserin is thought to reduce weight by targeting the serotonin (5HT2c) system to induce satiety. Lorcaserin IR has been shown to be effective in reducing weight in overweight (body mass index [BMI] > 27 kg/m2) and obese (BMI > 30 kg/m2) participants in three large Phase III trials. In addition, lorcaserin has been shown to reduce post-cessation weight gain and improved smoking cessation in a randomized placebo-controlled trial. A recent meta-analysis suggested in overweight diabetic patients lorcaserin may be added to first-line oral hypoglycemic medications to enhance reduction in glycated hemoglobin. Lorcaserin is generally well tolerated with the most common side effect being headache, which is typically self-limiting. Lorcaserin XR (once daily) was recently approved and has been shown to be bioequivalent to lorcaserin IR (twice daily) in a pivotal study. Lorcaserin XRs, main advantage over the IR formulation is the once daily dosing regimen, which likely would lead to improved adherence and thus improved clinical effectiveness. The present review will evaluate the lorcaserin clinical studies (obesity, diabetes, and addiction), XR bioequivalence studies, pharmacogenomics of the serotonin (5HT2c) system, and adherence data in once daily versus twice daily medications. Keywords: lorcaserin, Belviq©, obese, pharmacotherapy